218k views
4 votes
SOMEONE please help!!

SOMEONE please help!!-example-1

1 Answer

0 votes
So you are given a recursive series, which is an equation that writes itself. Now we want to create a explicit rule. Explicit rule is a pattern that uses our first term and add our common difference. So it gives us our first term.
a_(1) = -3

Lets find the second term of the recursive series.

a_2 = -3 +7 = 4

So it is increasing by 7

So our explicit rule is:

a_n = -3 + 7(n-1)
User Gershon Herczeg
by
5.9k points